Kemampuan Ekstrak Daun Sembung Rambat (Mikania micrantha H.B.K) Sebagai Bioherbisida Gulma Melastoma affine D.Don - Riza Linda, Hamidah HS, Mukarlina (Universitas Tanjungpura, 2015)
Bittervine (Mikania micrantha) is a kind of weed containing allelochemical compounds which can supressgrowth of plants nearby, so that Bittervine can potentially be used as bioherbicide. This research aims to testthe potentiality and effective concentration of M. micrantha leaves extract in inhibiting seeds germination and supressing growth of Blue tongue (Melastoma affine) weeds. This research was conducted at Biology Laboratory, Chemistry Laboratory and Green house facility of Math and Science Faculty of Tanjungpura University from May to September 2014. Completely Randomized Design was used in this research with extract concentration at 0 (g/ml), 0,17 (g/ml), 0,43 (g/ml), 0,82 (g/ml) and 1,5 (g/ml), each with three duplications. The result shows that the leaves extract of M. micrantha can inhibit seeds germination and supress the growth of M. affine weeds. The extract effective concentration that can lower the germinationpercentage and sprout length of M. affine was at 0,43 (g/ml). The extract effective concentration that can supress the growth of M.affine encompassing plant height, wet weight and dry weight was at 0,17 (g/ml).